Development of Anecopbl Model to Improve Critical Thinking and Collaboration Skills of Elementary School Students - Safitri, Irma Yulianti Budi; Prasetyo, Zuhdan Kun; Anjarsari, Putri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to develop anecopbl learning model to improve critical thinking and collaboration skills of elementary school students. This type of research is development research. The development model used in this study is the ADDIE model through 5 stages, namely, (1) analysis stage (2) design stage; (3) development stage (4) implementation stage,; (5) evaluation stage. The data obtained in the validation of model assessment instruments by experts are in the form of underlying theories, objectives, syntax, and social systems. The results of the conversion of validation assessments on the underlying theoretical aspects have an average value of 10 with very good categories. While the conversion results of the validation assessment on the objective aspect have an average of 8.5, with a very good category. The results of the conversion validation assessment on syntax and social systems by experts have an average value of 18.5 so that it has a very good category. The effectiveness of the anecopbl model was shown by an average test result of n-gain of 0.77 in the effective category. These results suggest that the use of models can improve students' critical thinking skills. Based on the effect size test between the control group and anecopbl showed a result of 2.90 showing that learning using the model that has been done is very effective and has a major effect in improving critical thinking skills. The results of the collaboration assessment showed that more than half of all respondents agreed that they had the same goals, shared duties and responsibilities, and that there was cooperation between groups. So that the anecopbl model is feasible, effective, and practical to be used to improve critical thinking and collaboration skills of elementary students. Keywords: anecopbl, critical thinking, collaboration